Employee satisfaction on performance appraisal: a study on perception of employees at Putra Specialist Hospital (Melaka) Sdn Bhd / Nurul Farehah Rozahan - Rozahan, Nurul Farehah (2009)
The purpose of this study is to determine the perception of employees towards performance appraisal system that applied in Putra Specialist Hospital (Melaka) Sdn Bhd (PSH). It concerns about the employee’s satisfaction with the system. The approximate number of employees in PSH is 300 and above whereby involves nurses, doctors and other administration workers. Employee evaluation or also known as performance appraisal is critical to the functioning of an organization and advancement of employees. In PSH, employees will be reviewed to determine the level of work perform whether achieving the standards or not while in the same time rewarding the high performer and given additional opportunity for low performer to improve themselves. During the analysis, 71 questionnaires have been distributed to the employees to determine their perception. By using three independent variables that can influence the satisfaction of employees which are feedback, reward or outcome and experience with the system, the analysis has shown that feedback is the most influence variable. Most employees have agreed that both appraiser and appraisee need to share and discuss the feedback from the evaluation performed. Even though they had agreed with the role of feedback for their satisfaction, other variable also influence them such as reward being given and experience they had with the system. The questionnaires were embrace in 3 sections which are demographic, perception on performance appraisal and satisfaction with the system.